Various Problems in Accepting RV Vaccines in Southeast Nations: A Literature Review - RATNA DELILA; Alpha Fardah Athiyyah; Manik Retno Wahyunitisari (Journal of Community Medicine and Public Health Research, 2026)
According to Southeast Asian rotavirus surveillance statistics from 2008 to 2018, rotavirus infection was responsible for 40.78% of all diarrhea cases. Rotavirus-induced acute diarrhea is a significant cause of illness and mortality among children under five in Southeast Asia. According to efficacy studies, the rotavirus vaccine can offer heterotypic protection against different genotypes and lower the incidence of diarrhea and death even in cases where vaccination is insufficient. The purpose of this study was to provide an overview of how Southeast Asian nations react to the rotavirus vaccine. The method used in this study was a nonsystematic review conducted according to gathering literature based on the keywords “rotavirus vaccine acceptance”. Literature chosen from PubMed, ScienceDirect, and Google Scholar. Similar difficulties were encountered when delivering the rotavirus vaccination to the general public in Southeast Asian countries such as Indonesia, Malaysia, the Philippines, and Thailand. These barriers include public skepticism over the RV vaccine's efficacy, safety, and halal status (in accordance with Islamic sharia law), as well as the vaccine's high cost before its implementation as a national vaccination program, particularly in nations that do not adhere to GAVI regulations. The public in several Southeast Asian countries has not fully embraced the rotavirus vaccination, particularly in the early stages of its introduction, according to an analysis of seven papers.